Graphene Solar Cells-Will it be the Ultimate Power Converter? - Arghya Narayan Banerjee (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2015)
Solar cells or photovoltaic (PV) cells involve the direct conversion of light energy into electrical energy. PV cells are basically p-n junctions made from layers of semiconducting materials. Under light illumination, either free electron-hole pairs are generated within the bulk of the layers and subsequently separated through the internal electric field across the depletion layer of the junction (in conventional solar cells), or exactions are created and simultaneously separated across a hetero-interface (in excitonic solar cells), thus producing an open-circuited photo voltage [1,2]. Upon connection with an external circuit, an electric current is drawn out and used for powering outside devices. This photocurrent, along with the photo voltage, defines the power that the solar cell can deliver.